Microbial activity and hard red spring wheat growth improvement following biostimulant application - Zachary J. Bartsch; Thomas M. DeSutter; Caley K. Gasch (Agrosystems, Geosciences & Environment, 2023)
Abstract Reclamation of oil and gas disturbed soils is challenging due to diminished function (i.e., soil physical, chemical, and biological properties) from the loss of soil organic carbon (SOC) and potential mixing of topsoil and subsoil. Biostimulants are agro‐products applied to soil to improve SOC formation, microbial nutrient cycling, and crop yields, suggesting their potential use in reclaiming oil and gas disturbed soils. However, studies on the ability of biostimulants to enhance reclamation in disturbed soils are limited. Therefore, research was conducted to determine if biological properties were affected by biostimulant products in soil collected from an active pipeline installation project. The study was conducted in a greenhouse using pots consisting of the following soil treatments: TS100 (100% topsoil), TS50 (1:1 by‐weight subsoil/topsoil), TS25 (3:1 subsoil/topsoil), TS12.5 (7:1 subsoil/topsoil), and TS0 (100% subsoil). Blended soil either received a liquid inoculant or biotic mulch biostimulant and were planted with hard red spring wheat (Triticum aestivum) later on. Soil biological properties were generally influenced by topsoil concentration where TS50 consistently produced similar results to TS100, however, nitrogen (N) and phosphorus (P) were also influenced by biostimulant treatment. Additionally, wheat biomass was significantly greater in the liquid treatment, whereas the biotic mulch stimulated greater microbial abundance and activity. Overall, increased topsoil improved biological recovery in the short term, and the addition of biostimulants in blended soils can also enhance recovery regardless of topsoil content. However, it is unclear whether the recovery is sustained into the long‐term without additional biostimulant application.